EFFECTS OF PHYTOESTROGENS ON MAMMALIAN REPRODUCTIVE PHYSIOLOGY - Socorro Retana-MÃ¡rquez; Horacio HernÃ¡ndez; JosÃ© A. Flores; Minerva MuÃ±oz-GutiÃ©rrez; Gerardo Duarte; JesÃºs Vielma; Gonzalo Fitz-RodrÃguez; Ilda FernÃ¡ndez; Matthieu Keller; JosÃ© A. Delgadillo (Tropical and Subtropical Agroecosystems, 2011)
Global consumption of phytoestrogens and their effects have increased both in animals and humans due to the augmented use of legumes in animal diets as well as the increase in vegetarian diets in some human populations. Even though the general opinion and that of clinicians toward phytoestrogens is generally positive, many phytoestrogens are now recognized as endocrine disruptor compounds, capable of interfering with the synthesis, secretion, transport, binding, action or elimination of natural hormones in the body that are responsible for reproduction. The effects of phytoestrogens mainly depend on the type, amount and plant species ingested. These compounds are found widely in a variety of plants and fodder, and can have adverse effects mainly on the reproductive tract in most animal species. Many phytoestrogens can act as estrogenic agonists or antagonists, and their effects can vary from infertility to an estrogenic over-response, thus increasing secretions in the reproductive tract and disrupting animal behavior. Presently, there is still a lack of knowledge on this subject, and the effects on reproductive parameters of estrogenic forage in animal production systems are unknown. Therefore, it is necessary to continue research in order to elucidate the effects of phytoestrogens, the doses at which effects are seen, the species, the disruptive or beneficial effects, as well as the mechanisms of action involved. This review focuses on the effects of phytoestrogens in the reproductive physiology of livestock and human, as well as the knowledge obtained from research in animal models.